Effects of Dietary Inclusion of Lentil Byproduct on Performance and Oxidative Stability of Eggs in Laying Quail - Metin Çabuk; Serdar Eratak; Hatice Basmacioğlu Malayoğlu (The Scientific World Journal)
One hundred and sixty-eight 11-week-old laying quails (Coturnix coturnix japonica) were fed one of the following three diets: (1) control: basal diet with no lentil (Lens culinaris L.) byproduct; (2) inclusion of 10% lentil byproduct; (3) inclusion of 20% lentil byproduct. In the recent years, colour sorting machines are used in order to separate red lentils according to their colours. The goal is to select the items which are discoloured, not as ripe as required, or still with hull even after dehulling of lentil seed. During the sorting, a new byproduct called “sorting byproduct” leftover is obtained. The byproduct is cleaner and is of a higher quality than other lentil byproducts. This experiment was conducted to study the effects of the inclusion of different levels of lentil byproduct on laying quail performance. The experimental treatment included 10% or 20% lentil byproduct in the diet, and this was fed to quails aged between 11 and 22 weeks. The inclusion of 10% and 20% levels of lentil byproduct in the diet significantly increased egg production, but feed intake and feed conversion ratio were not significantly affected. Egg weight decreased significantly following the inclusion of 20% lentil byproduct. The inclusion of lentil byproduct in the diet increased the deposition of yellow yolk pigments and decreased malonaldehyde formation in the yolk.